The Intersection of Philosophy and Literature: Exploring Ideas and Reality (PANOPTICON: Journal of English Studies, 2024)
The study of literary philosophy is a relatively new field in Indonesia, though it cannot be said to be a completely new discipline globally. There is growing optimism that the philosophy of literature will attract significant interest due to its unique advantages and distinct focus. This field explores the intersection of philosophy and literature, encompassing both written and oral traditions. This intersection offers a rich area for exploration, both in the realm of ideas and the tangible world. Philosophy and literature both concern themselves with the human experience, examining relationships between individuals, the divine, nature, life, and various existential issues. As a new branch of its parent discipline, the "Philosophy of Literature" joins other specialized fields such as the philosophy of language, law, economics, politics, education, development, medicine, communication, culture, management, religion, and more. In the future, literature is likely to be increasingly studied as a philosophical subject, although some argue that philosophical values have always been inherent in literary works, making the relationship between philosophy and literature a form of 'acronym.' In the digital era, as modern humans become increasingly dependent on digital communication and information, both written and spoken languages continue to evolve. They now often appear on the screens of tablets, cellphones, laptops, computers, and televisions. The challenges and impacts of digital language are significant, affecting not only language and literature but also linguistic and literary philosophy..